PENANAMAN ADAB SANTRI DALAM PENDIDIKAN ISLAM: PROBLEMATIKA DAN UPAYA IMPLEMENTASI DI KUTTAB DARUL ULUM SERANG SUMBEREJO - Rifka Kurnia; Rahmat Setiawan (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the problems in instilling moral values (adab) among students at Kuttab Darul Ulum and the efforts made to address them. This research employed a qualitative approach using interviews with the school principal as the primary data source. The findings indicate that the cultivation of adab is the main focus of the educational process, aiming to develop students who are polite and well-mannered, particularly in their interactions with parents, teachers, and peers. The implementation is carried out through habituation, the application of standard operating procedures (SOP), and continuous guidance for students. However, several challenges were identified in the implementation process, including the lack of optimal role modeling by some teachers, the influence of family environments, and the impact of technological developments such as the use of gadgets and social media. To address these issues, the school has taken various measures, including providing educational guidance for teachers and establishing collaboration with parents through parenting programs. Although the effectiveness of these programs has not yet reached optimal levels, the findings show positive responses from parents regarding improvements in children’s behavior. This study concludes that the cultivation of adab requires collaboration among schools, teachers, and parents, as well as consistent and continuous efforts. Therefore, strengthening teacher role modeling, supervising the use of technology, and developing innovative learning strategies are necessary to improve the quality of moral education in the future. ABSTRAK Penelitian ini bertujuan untuk menganalisis problematika penanaman adab santri di Kuttab Darul Ulum serta upaya yang dilakukan dalam mengatasinya. Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara dengan kepala sekolah sebagai sumber utama data. Hasil penelitian menunjukkan bahwa penanaman adab menjadi fokus utama dalam proses pendidikan, dengan tujuan membentuk santri yang sopan dan beradab, khususnya kepada orang tua, guru, dan sesama teman. Implementasi dilakukan melalui pembiasaan, penerapan aturan (SOP), serta pembinaan terhadap santri. Namun, dalam pelaksanaannya terdapat beberapa kendala, di antaranya kurang optimalnya keteladanan pengajar, pengaruh lingkungan keluarga, serta dampak perkembangan teknologi seperti penggunaan gadget dan media sosial. Untuk mengatasi permasalahan tersebut, pihak sekolah melakukan berbagai upaya, seperti memberikan edukasi kepada guru dan menjalin kerja sama dengan orang tua melalui kegiatan parenting. Meskipun efektivitas program belum maksimal, hasil penelitian menunjukkan adanya respons positif dari wali santri terhadap perubahan perilaku anak. Penelitian ini menyimpulkan bahwa penanaman adab memerlukan kerja sama antara sekolah, guru, dan orang tua serta dilakukan secara konsisten dan berkelanjutan. Oleh karena itu, diperlukan penguatan keteladanan pendidik, pengawasan penggunaan teknologi, serta inovasi dalam pembelajaran untuk meningkatkan kualitas penanaman adab di masa mendatang.